External Morphological Study of Tabanus nemoralis Meigen 1820 (Diptera: Tabanidae). In Baghdad/ Iraq - Sabr, Ahmed Jameel; Aljaf, Mouhannad Mahmood (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
This work included external morphological study of horse fly Tabanus nemoralis Meig. 1820, which belongs to family Tabanidae order: Diptera. The study involved the most important taxonomic external characters of the: head, thorax, abdomen and their appendages which are: antenna, maxillary palp, wings, legs, spotting in coloring pattern of abdomen